The Impact of Political Institutions on Fiscal Sustainability in NMS 11 Countries: Mediating Effects of Economic Reforms - Ganic, Mehmed; Brankovic, Azra (Ekonomika, 2025)
The aim of this study is to investigate how the link between a country’s legislative and executive branches affects its ability to maintain fiscal discipline through mediating effects of economic reforms. The research bases its analysis on an investigation of NMS-11 countries between 1991 and 2022 using Quantile Mediation Analysis (QMA). It begins with an estimation of the impact of political institutions on fiscal sustainability and then continues with an investigation of the ways how political institutions influence the implementation of economic reforms through a mediator model. Moreover, in an attempt to evaluate the mediation effect, the study uses relevant coefficients taken from prior analyses to compute the indirect impact across quantile distributions. The study sheds the importance of the context in evaluating the role of political institutions and economic reforms on fiscal sustainability, highlighting the varying effects at different quantile levels. In fact, economic reforms are shown to be important when fiscal stress is at a relatively low level and are relatively less effective when the stress is high because the impact of the reforms and institutional factors differs according to the distribution of debt to GDP. This investigation shows that political stability and fiscal outcomes are interactive by segmenting this group into legislative, executive, judicial, and federal dimensions. Politicians should focus on improving the democratization processes of the lower house to facilitate accountability and decision-making when it comes to the judiciary to assist in fiscally integrating during some rough patches. They should also use specific economic actions regarding debt as well as apply the federal policies relevant to various forms of federalism to provide successful reforms.